Nalar Hermeneutika Farid Essack dalam Membangun Solidaritas Kebangsaan - Zainuddin, Ammar (Proceedings of Annual Conference for Muslim Scholars, 2019)
This article aims to understand the concept of hermeneutics initiated by a professor in the field of tafsir. He is named Farid Esack, has tried to find a solution of change for the people oppressed by the Apartheid regime at that time. Hermeneutics liberation is not just a theoretical concept, even its applicability is a solidarity of liberation. From a reflection and liberation solidarity movement, just being tolerant is not enough. A praxis, inter-religious dialogue is a solution that it considers to generate the spirit of freedom of the people of North Africa. In Indonesia, conflicts over religion-name, sectarianism, and strife can still be found in the community. So by dialogue, discussion together solve the problem to seek a better and appropriate point when applied in Indonesia multicultural society. It should be noted, however, that the implication of the concept offered by Esack is that the interpreter must have the courage to study the contents of the Qur'an in a rational way as well as being an actor in national activities to establish solidarity in the life of the nation.